Parenting strategies and child behavior in children with Down syndrome - Lopez, Amber, author; Fidler, Deborah, advisor; Daunhauer, Lisa, committee member; Lunkenheimer, Erika, committee member; Sample, Pat, committee member (Colorado State University. Libraries, 2014)
This study examined parent-child interactions in Down syndrome in the context of a collaborative puzzle task. Variables of interest included the parent dimensions of teaching and directives, and the child behaviors of compliance, persistence, and social engagement during a five-minute interaction. Based on previous research in the field of parenting and developmental disabilities, it was hypothesized that parents of children with Down syndrome would exhibit significantly more directive behavior than parents of typically developing children, and that the use of directives would be associated with higher levels of compliance and task persistence in children with Down syndrome. It was also hypothesized that children with Down syndrome would engage in higher levels of off-task behavior, such as social engagement with a parent, based on evidence of the over-use of social behaviors during challenging tasks in this population. Children with Down syndrome (N = 20) and mental-age matched typically developing children (N = 13), and their parents, were recorded during a five-minute problem-solving task. Parent and child behaviors were captured utilizing a modified version of Lunkenheimer's (2009) Dyadic Interaction Coding System. Results indicated that parents of children with Down syndrome demonstrated both significantly higher levels of directive behaviors and teaching behaviors in comparison to parents with typically developing children. Contrary to previous research, children with Down syndrome in this study were found to be significantly more compliant than their typically developing peers, and no significant differences emerged between the groups in terms of off-task, socially-related behavior. Additionally, this study examined the reciprocal nature of parent-child interactions using state lag sequential analyses. Results from these analyses demonstrated a higher probability of directive parenting behavior following child social engagement in the Down syndrome group as compared to the typically-developing group. Conversely, the lag sequential analyses demonstrated a higher probability of teaching parent behavior following social engagement in the typically-developing group as compared to the Down syndrome group. The likelihood for both teaching and directive parenting behavior following child noncompliance was also higher in the Down syndrome group as compared to the typically-developing group. The findings from this study demonstrate consistency with previous work that parents of children with Down syndrome are more directive than parents of typically developing children, and highlights the differing patterns of parenting behavior in both typically and atypically developing populations. The use of analyses to examine dyadic contingencies also provides new information regarding the strategies that parents employ with their children to promote on-task behavior, specifically in children with an intellectual disability. Lastly, this study contributes to the body of research on the behavioral phenotype of children with Down syndrome.